Native and prosthetic graft infections of the thoracic aorta: surgical management. (30th March 2021) - Rustum, Saad; Beckmann, Erik; Martens, Andreas; Krüger, Heike; Arar, Morsi; Kaufeld, Tim; Haverich, Axel; Shrestha, Malakh Lal
Abstract: : OBJECTIVES: Infection of the native aorta or after previous open or endovascular repair of the thoracic aorta is associated with high risks for morbidity and mortality. We analysed the outcome after surgical management of a native mycotic aneurysm or of prosthetic graft infection of the descending aorta. METHODS: From June 2000 to May 2019, a total of 39 patients underwent surgery in our centre for infection of the native descending aorta ( n = 19 [49%], group A) or a prosthetic descending aorta [ n = 20 (51%), group B]. In the 20 patients in group B, a total of 8 patients had prior open aortic repair with a prosthesis and 12 patients had a previous endovascular graft repair. RESULTS: The cohort patients had a mean age of 57 ± 14; 62% were men ( n = 24). The most common symptoms at the time of presentation included fever, thoracic or abdominal pain and active bleeding. Emergency surgery was performed in 11 patients (28%); 3 patients had emergency endovascular stent grafts implanted during thoracic endovascular aortic repair for aortic rupture before further open repair. The 30-day mortality was 42% in group A and 35% in group B. The 90-day mortality was 47% in group A and 45% in group B. Pathogens could be identified in approximately half of the patients (46%). The most commonly identified pathogens were Staphylococcus aureu s in 6 patients (15%) and Staphylococcus epidermidis in 4 patients (10%). Survival of the entire group (including patients with both native and prosthetic graft infections) was 44 ± 8%, 39 ± 8% and 39 ± 8% at 1, 2 and 3 years after surgery. The percentage of patients who survived the initial perioperative period was 81 ± 9%, 71 ± 9% and 71 ± 10% at 1, 2 and 3 years after surgery. CONCLUSIONS: Patients with infection of the descending aorta, either native or prosthetic, are associated with both high morbidity and mortality. However, patients who survive the initial perioperative period have an acceptable long-term prognosis. In emergency situations, thoracic endovascular aortic repair may help to stabilize patients and serve as bridge to open repair.